On Homogeneous Cubic Equation with Fourunknowns x3+y3= 2lzw2 - Gopalan, M.A; Vidhyalakshmi, S; Thiruniraiselvi, N (Review of Information Engineering and Applications, 2014)
The homogeneous cubic equation with four unknowns represented by the Diophantine equation x3+y3= 2lzw2 is analyzed for its patterns of non – zero distinct integer solutions. A few interesting properties between the solutions and special numbers, namely, Polygonal number, Pyramidal number, Centered polygonal number, Stella octangular number and Octahedral number are presented.